in Guide the sum of 65 and 2 by theirs Interne
Answers
Answered by
1
Step-by-step explanation:
First we have to find the sum (65/12)+(8/3)
LCM of 12 and 3 is 12
Then,
(65×1)/(12×1)=(65/12)
and (8×4)/(3×4)=(32/12)
Now,
=(65+32)/12
=(97/12)
Now find the difference of (65/12)−(8/3)
LCM of 12 and 3 is 12
Then,
(65×1)/(12×1)=(65/12)
(8×4)/(3×4)=(32/12)
Now,
=(65−32)/12
=(33/12)
Now divide (97/12)÷(33/12)
=(97×12)×(12/33)
=(97×12)/(12×33)
=(97×1)/(1×33)
=(97/33)
Answered by
1
Hope it will help you
Make me as brilliant
Attachments:
![](https://hi-static.z-dn.net/files/d3a/28338ad1867aea724fa020090a59a3c0.jpg)
![](https://hi-static.z-dn.net/files/d04/54c069683981a443f4bf0aaa16a1357f.jpg)
Similar questions